Preparation and thermal characterization of inclusion complex of Brazilian green propolis and hydroxypropyl-beta-cyclodextrin - Rocha, Bruno Alves; Rodrigues, Marina Rezende; Pires Bueno, Paula Carolina; de Mello Costa-Machado, Ana Rita; Lima Leite Vaz, Mirela Mara de Oliveira; Nascimento, Andresa Piacezzi; Barud, Hernane Silva [UNESP]; Berretta-Silva, Andresa Aparecida (Springer, 2012)
The propolis produced in Southeastern Brazil is known as green propolis (BGP) because of its color and the most important plant source is Baccharis dracunculifolia. Several authors reported biological activities such as anti-ulcer, anti-inflammator, antimutagenic, antifungal/antibacterial, antileishmanial/antiplasmodial for the BGP. For this reason, BGP has been extensively employed in food and beverages, thus helping improve health and preventing diseases. Some authors related that the biological activities of BGP are mostly due to its high levels of prenylated rho-coumaric acids derivatives, mainly artepillin C. The inclusion complex between Brazilian green propolis (BGP) with hydroxypropyl-beta-cyclodextrin (HP-beta-CD) was prepared and its characterization was investigated by different analytical techniques (X-ray diffraction, Fourier transform infrared spectroscopy, and thermogravimetry) and suggesting that propolis was molecularly dispersed in the HP-beta-CD matrix. The increasing solubility of chemical constituents was determined using quantitation methods for total flavonoids and polyphenols. Furthermore, it was developed a method for the quantitation and identification of the main compounds by high-performance liquid chromatography in order to evaluate the increasing water solubility of each constituent in aqueous BGP extract (aromadendrin, isosakuranetin, and artepillin C). The antioxidant activity was evaluated by chemical assay 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging.
Keywords: Brazilian green propolis; Hydroxypropyl-beta-cyclodextrin; Inclusion complex; Flavonoids; Polyphenols; Artepillin C